Selective hydrogenation by novel composite supported Pd egg-shell catalysts - Carrara, Nicolás Ricardo (2015)
Two organic–inorganic mixed phase supports were prepared, comprising an alumina filler and polymers of different chemical nature. Four low loaded Pd catalysts were prepared. Good activities and selectivities were obtained during the hydrogenations of styrene, 1-heptyne and 2,3-butanedione. The catalysts were found to have excellent mechanical properties and could be used in applications needing high attrition resistance and crushing strength. In this sense, processes for fine chemicals using slurry reactors or processes for commodities using long packed beds could advantageously use them.